2016
DOI: 10.3390/ijms17060905
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Inhibitor Insufficiently Attenuates HSC Senescence Administered Long-Term after 6 Gy Total Body Irradiation in Mice

Abstract: Senescent hematopoietic stem cells (HSCs) accumulate with age and exposure to stress, such as total-body irradiation (TBI), which may cause long-term myelosuppression in the clinic. However, the methods available for long-term myelosuppression remain limited. Previous studies have demonstrated that sustained p38 mitogen-activated protein kinases (p38 MAPK) activation in HSCs following exposure to TBI in mice and the administration of its inhibitor twenty-four hours after TBI may partially prevent long-term mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In contrast to acute myelosuppression, long-term BM suppression is manifested by a decrease in HSCs reserves and a defect in HSCs self-renewal; moreover, long-term BM suppression is long-lasting and exhibits little tendency for recovery. Previous studies have demonstrated that exposure to high doses of irradiation caused long-term bone marrow injury, in part, by selectively inducing HSCs senescence [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to acute myelosuppression, long-term BM suppression is manifested by a decrease in HSCs reserves and a defect in HSCs self-renewal; moreover, long-term BM suppression is long-lasting and exhibits little tendency for recovery. Previous studies have demonstrated that exposure to high doses of irradiation caused long-term bone marrow injury, in part, by selectively inducing HSCs senescence [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…The body weight of mice did not decrease much, and their body condition was good in the 0 Gy irradiated group; however, the mice in the 2.5 Gy group survived approximately 17 days and were in poor condition, dying easily, which is unfavorable for the study of drug e cacy or the mechanism of HLL development. Importantly, irradiation can brie y result in serious myelosuppression [25] and lead to an inability to clearly observe leukemic cells in blood smears and bone marrow smears, making it di cult to assess whether the model was successful. Moreover, myelosuppression seriously affects routine blood tests and cannot truly allow the evaluation of changes in WBCs [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…13 Therefore, development of an effective method and drug to mitigate the radiation-induced intestinal injuries needs to be explored. Many studies have reported that Chinese herbal medicines or extracts and other drugs may be able to reduce TBI-induced injuries in the brain, oesophagus and haematopoietic system of irradiated animals, [14][15][16][17][18] but the study of protective drugs in IR-induced intestinal injuries still needs to be improved. [19][20][21] In the present study, we observed that the new compound XH-105 had protective effects on radiation-induced intestinal injuries.…”
Section: Discussionmentioning
confidence: 99%